Crystallaria cincotta, a new species of darter (Teleostei: Percidae) from the Elk River of the Ohio River drainage, West Virginia - Welsh, Stuart A.; Wood, Robert M. (Zootaxa, 2008)
A new species of percid, Crystallaria cincotta, is described from the Cumberland, Elk, Green, and Muskingum river drainages of the Ohio River basin, USA. It differs from populations of Crystallaria asprella of the Gulf Coast, lower Mississippi River, middle Mississippi River, upper Mississippi River, and Wabash River drainages by having a reduced number of cheek scale rows restricted to the post-orbital region, a falcate margin on the pelvic fins, a preorbital blotch distinctly separate from the anterior orbital rim, and a wide mouth gape. The Elk River population is also divergent genetically from populations of the Gulf Coast, lower Mississippi River, and upper Mississippi River drainages. Crystallaria cincotta, discovered in the Elk River of the Ohio River drainage in 1980, is a rare species with the only extant population represented by 12 individuals collected from 1980–2005 from the lower 36 km section of the Elk River, West Virginia.